Emotion embodiment in robot-assisted rehabilitation system using hybrid automata - Sidek, Shahrul Na'im; Ghazali, Aimi Shazwani; Wok, Saodah (2014)
The embodiment of emotions in the paper is structured under hybrid automata framework. In particular, the paper focuses on the description of the automata model designed for robot-assisted rehabilitation system in term of its initialization value, modes, condition for each mode, guard conditions, and transition between modes. A structured experimental setup was designed to evaluate the performance of the hybrid automata proposed. The result demonstrates the efficacy of hybrid automata approach in the rehabilitation application where emotion of the subject is taken into consideration in deploying suitable rehabilitation tasks.